An Effective Rank Based Ant System Algorithm for Solving the Balanced Vehicle Routing Problem - Yousefikhoshbakht, Majid; Didehvar, Farzad; Rahmati, Farhad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
The vehicle routing problem (VRP) is one of the most significant problems of the operational research problems which has numerous applications in industrial and service problems. The VRP is the problem of designing optimal delivery from a given depot in order to satisfy the demand of the customer population by a similar fleet of vehicles. It is noted that a considerable part of the drivers’ benefits is related to their traveled distance; therefore, the balance of the route based on vehicles’ traved distance is important to obtain drivers’ satisfaction. This paper presents a balance based on the vehicles’ traveled route called balanced vehicle routing problem (BCVRP) and then a model integer linear programming is proposed for the BCVRP. Because solving of this problem as same as VRP is difficult, an effective rank based ant system (ERAS) algorithm is proposed in this paper. In addition, to show the efficiency of the proposed ERAS, a number of test problems in both small and large scales involving 10 to 199 customers have been considered and solved. The computational results show that the proposed algorithm results are better than results of classical rank based ans system (RAS) and exact algorithm for solving the BCVRP within a comparatively shorter period of time.